Deep Learning and Competition in Psycholinguistic Research - Taraban, Roman; Тарабань, Роман; Marshall, Philip H.; Маршал, Філіп Х. (My University, 2018)
MacWhinney, Bates, and colleagues developed the Competition Model in the 1980s as an alternate to Chomskyan models that encapsulate syntax as a special-purpose module. The Competition Model adopted the functional perspective that language serves communicative goals and functions. In contrast to the premise that knowledge of language is innate, the Competition model asserts that language is learned and processed through general cognitive mechanisms that identify and weight phonological, morphological, syntactic, and semantic cues in the language experiences of the learner. These weighted cues guide the language user in the comprehension and production of language forms. The present article provides background on the Competition Model, describes machine simulations of linguistic competition, and extends the principles of the Competition Model to new machine models and applications through deep learning networks.Б. МакВінні, Е. Бейтс разом із колегами розробили модель конкуренції в 1980-х роках як альтернативу моделям Н. Чамського, які містять синтаксис як спеціальний модуль. Модель конкуренції започаткувала функціональну перспективу, відповідно до якої мова слугує комунікативній меті та функціям. На відміну від положення про те, що знання мови – вроджене, модель конкуренції постулює, що мова вивчається й обробляється за допомогою загальних когнітивних механізмів, які ідентифікують та «взважують» фонологічні, морфологічні, синтаксичні та семантичні сигнали в мовному досвіді суб’єкта навчання. Ці сигнали скеровують користувача мови до розуміння та породження мовних форм. Цю статтю присвячено опису основ моделі конкуренції, машинного моделювання мовної конкуренції. Автори спробували поширити принципи конкурентної моделі на нові машинні моделі та додатки за допомогою мереж поглибленого навчання.
Поглиблене навчання та конкуренція в психолінгвістичних дослідженнях
Keywords: deep learning; Competition Model; cues; machine learning; поглиблене навчання; сигнали; модель конкуренції